Probabilistic safety evaluation of a concrete arch dam based on finite element modeling and a reliability L-R approach - Pouraminian, Majid; Pourbakhshian, Somayyeh; Noroozinejad Farsangi, Ehsan; Fotoukian, Reza (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The safety assessment of the Pacoima arch dam is investigated in this paper. A Load - Resistance (L-R) method was used to ensure that the dam is safe or if it is at risk of failure. The "probabilistic design system" ANSYS finite element software was used to calculate the probability of failure. The Monte Carlo (MC) method with 50,000 iterations utilized for simulation and the Latin Hypercube method were used for Sampling.
Keywords: Pacoima arch dam; safety evaluation; Monte Carlo simulation; hydrostatic pressure; random variables; worst case; zapora łukowa Pacoima; ocena bezpieczeństwa; symulacja Monte Carlo; ciśnienie hydrostatyczne; zmienne losowe